From the jaws of the "Leviathan": A sperm whale tooth from the Valencina Copper Age Megasite. - Samuel Ramírez-Cruzado Aguilar-Galindo; Miriam Luciañez-Triviño; Fernando Muñiz Guinea; Luis Miguel Cáceres Puro; Antonio Toscano Grande; Marta Díaz-Guardamino; Juan Manuel Vargas Jiménez; Thomas Xavier Schuhmacher; Rafael María Martínez Sánchez; Santiago Guillamón Dávila; Joaquín Rodríguez Vidal; Leonardo García Sanjuán (PLoS ONE)
During the excavations undertaken in 2018 at the Nueva Biblioteca sector of the Valencina Copper Age mega-site, in south-west Spain, an exceptional sperm-whale tooth was found inside a non-burial pit. This remarkable object is the first of its kind ever found for Late Prehistoric Iberia. Due to its rarity and importance, a multidisciplinary study was carried out, including photogrammetric 3D modelling, as well as taphonomic, paleontological, technological and contextual analysis. This led to a full characterisation of the artefact through the analysis of its bioerosion traces, anthropogenic marks, depositional context and socio-cultural background. The ensuing discussion covers the history and processes the tooth went through from the death of the animal and disposal on the seabed, through the disarticulation of the tooth to its collection in a coastal environment and its subsequent use and deposition in the pit.